Construction of a prototype flotation cell pilot - Figueroa, Aquiles (2009)
The study is about the construction of a prototype from flotation cell pilot “San Marcos” to pilot level, for develop this the next activities has been performed: confection of planes from machine organs including necessary cuts, preparation of molds for fuse the pieces and other parts, assembly the flotation equipment, Install the cell in the circuits from pilot plant, and prove the suitable functioning for the equipment.